State Policy of Kazakhstan on Implementing of Renewable Energy Sources in Textile Industry Companies - Durru, Oguz; Yessengeldina, Anar; Kosherbayeva, Aigul; Shakeyev, Sayan; Shaikin, Dinmukhammed (International Journal of Energy Economics and Policy, 2021)
The article discusses the mechanisms of state support for the development of renewable energy sources (RES) in the Republic of Kazakhstan. The authors consider the prospects of using solar energy in the textile industry. The analysis revealed that the level of organization of work in companies in the field of energy conservation and energy efficiency of production depends on the following factors: timely observation of the current power supply and possible future energy potential; development and implementation of energy-effective measures; use of RES with purpose of saving energy resources. According to the authors, the dominance of electric and thermal forms of energy in the cost structure leads to a loss of competitiveness of the company’s products in the textile industry. The article considers the transition to combined generation of electric and thermal energy in textile industry companies using renewable energy sources. The calculation of the energy saving coefficients of electric and thermal energy produced by the authors proved the possibility of reducing the cost of textile products by introducing renewable energy sources. The results of the assessment, based on the construction of a correlation and regression model, showed the economic efficiency of using renewable energy in the textile industry, while the authors recommend paying special attention to state regulation of tariffs and the auction price for renewable energy. Keywords: renewable energy sources, solar energy, textile industry. JEL Classifications: Q42, Q48, L60 DOI: https://doi.org/10.32479/ijeep.10659